The complete mitochondrial genome of red-fronted parrot (Poicephalus gulielmi) revealed a new gene rearrangement within the order Psittaciformes - Adam Dawid Urantówka; Aleksandra Kroczak; Paweł Mackiewicz (Mitochondrial DNA. Part B. Resources, 2017)
Vertebrate mitogenomes are thought to be selected for compactness. Therefore, the increasing number of avian mitogenomes comprising duplicated regions is surprising. Such regions were proposed for at least 26 parrot genera based on the length of PCR products. However, complete mitogenomes with the duplications were shown only for six genera. These duplications evolved probably from the ancestral tRNATHR/tRNAPRO/ND6/tRNAGLU/CR and were subjected to subsequent degeneration. Here, we report the mitogenome of Poicephalus gulielmi (the subfamily Psittacinae) with a unique duplication tRNATHR/pseudoND6/CR1/tRNAPRO/ND6/tRNAGLU/CR2. This region is different from all other identified regions and resembles mostly the arrangements in Amazona and Pionus from the subfamily Arinae.